2019
DOI: 10.1097/iae.0000000000001995
|View full text |Cite
|
Sign up to set email alerts
|

Swept-Source Optical Coherence Tomography Angiography Assessment of Fellow Eyes in Coats Disease

Abstract: Fellow eyes of Coats patients carry quantitative foveal vascular alterations at SCP. These may represent markers of altered inner blood-retinal barrier, due to a bilateral defect in midcapillary angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
1
14
1
Order By: Relevance
“… 5 The study of macular changes in Coats disease determined by optical coherence tomography angiography (OCTA) has yielded inconclusive results concerning the laterality of Coats disease. 6 , 7 Schwartz et al 6 have shown significant differences in vascular density and foveal avascular zone (FAZ) when comparing affected and fellow eyes. Conversely, Stanga et al 7 have suggested that fellow eyes of Coats disease carry quantitative foveal vascular alterations compared with control eyes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 5 The study of macular changes in Coats disease determined by optical coherence tomography angiography (OCTA) has yielded inconclusive results concerning the laterality of Coats disease. 6 , 7 Schwartz et al 6 have shown significant differences in vascular density and foveal avascular zone (FAZ) when comparing affected and fellow eyes. Conversely, Stanga et al 7 have suggested that fellow eyes of Coats disease carry quantitative foveal vascular alterations compared with control eyes.…”
mentioning
confidence: 99%
“… 6 , 7 Schwartz et al 6 have shown significant differences in vascular density and foveal avascular zone (FAZ) when comparing affected and fellow eyes. Conversely, Stanga et al 7 have suggested that fellow eyes of Coats disease carry quantitative foveal vascular alterations compared with control eyes.…”
mentioning
confidence: 99%
“…; Stanga et al. ), which argues that the disease may affect both eyes, however, with a different susceptibility for or a delay between disease development in the two eyes. On the basis of this evidence, it might be hypothesized that the development of Coats’ disease could be related to impaired pressure autoregulation in retinal arterioles, which for some unknown reason leads to visible vasodilatation, hyperpermeability and exudation in one eye.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, each image (the original unaltered image as well as versions with each of the above changes) was separately binarized using the following methods, which were identified as representing a near-comprehensive list of binarization algorithms (with the exception of custom methods that could not be reproduced) used in past OCTA studies: Global default 10 , 11 , global Huang 12 , global IsoData 13 , global mean 14 , 15 , global Otsu 16 , local Bernsen 17 , 18 , local mean 19 , local median 12 , 20 , local Niblack 21 23 , local Otsu 24 , and local Phansalkar 25 28 . All local thresholds were applied with a radius of 15 pixels based on the methods used in prior studies on the same devices we employed 25 28 .…”
Section: Methodsmentioning
confidence: 99%